Pengaruh Citra Merek dan Ulasan Pelanggan terhadap Keputusan Pembelian Produk Elektronik di Tokopedia dengan Kepercayaan Konsumen Sebagai Variabel Moderasi: Studi pada Konsumen di Kabupaten Sragen - Agung Tri Rahmadi; Erni Widiastuti (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
This study investigates the influence of brand image and customer reviews on purchasing decisions for electronic products on the Tokopedia platform. A primary focus is placed on the role of consumer trust as a moderating variable, specifically within the geographical context of Sragen Regency. Adopting a quantitative research approach, the population comprises Tokopedia users in Sragen who have previously purchased electronic items. Through the application of a purposive sampling technique, 100 respondents were selected as the study sample, with primary data collected using structured questionnaires.Data processing was executed digitally utilizing IBM SPSS Version 25 for Windows. The analytical stages implemented include instrument quality testing through validity and reliability tests, descriptive analysis, multiple linear regression, F-tests, t-tests, and the coefficient of determination (R2). Additionally, Moderated Regression Analysis (MRA) was employed to examine the interaction effects of the moderating variable. Findings based on the t-test reveal that brand image (X1), customer reviews (X2), and consumer trust (Z) partially exert a positive and statistically significant influence on purchasing decisions (Y). Similar results were observed in the simultaneous testing. However, the moderation test yields a compelling finding: consumer trust is not significantly proven to strengthen or moderate the relationship between brand image or customer reviews and the final purchasing decisions made by consumers in Sragen.